PERLINDUNGAN HUKUM TERHADAP ANAK DARI KEJAHATAN PORNOGRAFI DI MASA PANDEMI COVID-19 - Dian Adriawan Dg Tawang; Maria Silvya E Wangg; Andi Widiatn; Rini Purwaningsih; Rita Pranawati; Putu Elvina (Faculty of Law, Trisakti University, 2021)
Covid 19 detected in Indonesia was overcome by establishing a policy of physical restrictions. All Ministries, including the Ministry of Education, issued Circular Letter Number 4 of 2020 concerning the Implementation of Educational Policies in the Emergency Period for the Spread of Coronavirus Disease (COVID 19). ECPAT Indonesia (End Child Prostitution, Child Prostitution) Pornography, & Trafficking of Children for Sexual Purposes) reports that during the COVID-19 pandemic, children experience various vulnerabilities when engaging in online activities. The Indonesian Child Protection Commission (KPAI) revealed data from 2011 to 2020 that children who were victims and perpetrators of pornography and cybercrime were 3178 children. and how is the law enforcement of cyber pornography crimes against children in the laws and regulations in Indonesia? The results of the study conclude that the protection of children against cyber crimes in Indonesia is not only penal but also non-penal by severing the network for the manufacture and distribution of child pornography cyber products, blocking pornography via the internet, monitoring the manufacture, distribution, and use of pornography; and cooperate and coordinate with various parties, both from within and outside the country, in preventing the manufacture, distribution, and use of pornography. Law enforcement of child pornography cybercrimes in Indonesia is based on Law No. 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, considering that Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection has not specifically regulated law enforcement for child pornography cyber crimes in Indonesia. Key Words: Protection, Children, Pornography and Covid -19